Aluminium and iron record for the last 28 kyr derived from the Antarctic EDC96 ice core using new CFA methods - Lorenzo Magaldi; I. Fattori; Carlo Barbante; Rita Traversi; Roberto Udisti; O. Largiuni; Vania Gaspari (Annals of Glaciology, 2004)
AbstractSpectrofluorimetric and spectrophotometric continuous flow analysis (CFA) methods were developed and applied to the determination of aluminium and iron in EPICA Dome C (East Antarctica) ice-core samples (6–585m depth). The methods are able to measure the fraction of Al and Fe which can be detected once the sample is filtered on a 5.0 μm membrane and acidified to pH 2. Both the methods present high sensitivity (detection limit of 10 ng L–1 for Al and 50 ng L–1 for Fe) and reproducibility (5% at sub-ppb level). The Fe and Al profiles show sharp decreases in concentrations in the last glacial/interglacial transition, reflecting the decreasing dust aerosol load. The two elements show a different pattern during the Antarctic Cold Reversal (ACR) climatic change, with high iron concentrations (similar to the glacial period) and low but increasing Al content during the ACR minimum. In order to interpret the Al and Fe data obtained by CFA, a comparison with Al and Fe composition, as measured by inductively coupled plasma sector field mass spectrometry (ICP-SFMS), was performed for Holocene, ACR and glacial periods. The percentage of CFA-Al with respect to ICP-SFMS-Al in the three periods shows a lower variability than CFA-Fe (3% in the glacial period and 64% in the ACR). This pattern may be explained by the different dominant iron sources in the different climatic periods. During the Last Glacial Maximum, Fe is proposed to arise mainly from insoluble continental dust, while a variety of ocean-recycled Fe, mainly distributed in fine particles and as more soluble species, shows a higher contribution in the ACR and, to a lesser extent, in the Holocene.